Coisas que aconteceram comigo (e com todos nós) : um estudo sobre o trauma histórico na Literatura - Diniz, Bianca Dias (2018)
Some historians agree that the terrorist attacks of September 11 marked the beginning of the 21st century. If the twentieth century was marked by two world wars, the 21st century was no better than its predecessor in terms of horror and violence. Consequently, art couldn’t fail to be contaminated by all of this. Thus the postmodern literature emerges, which resumes past tragedies in order to shed a new light on the catastrophes of the present. One of the most representative works of this new literary movement in the 21st century is Extremely loud and incredibly close, Jonathan Safran Foer’ second novel, published for the first time in 2005. In order to clarify the relationship between Literature, History and traumatic events, this work aims to examine the way in which the North American author represents these facts and their subjective consequences in the novel Extremely loud and incredibly close, based on concepts of psychology, history and literary theory.